Theory and practice in education - Hartley, Charles Pinckley (My University, 1892)
Introduction: In the process of education we find two great parts – one treating of material, and the other of immaterial things. Immaterial things are studied by means of the mind alone, while material things are most successfully studied by means of the mind in connection with the five senses. Now it is with these material things that the great mass of mankind are constantly working. Agriculture, manufacture and commerce are but different methods of treating tangible things; and it is natural, therefore, in order to satisfy material wants, that the first step toward education should be to become acquainted with the common things of the world—to understand our relation to them, and their relation to each other. To form this acquaintance, what is necessary? Is it enough that students should study about things? Certainly not, for with material things, as with members of a community, in order to form a thorough acquaintance it is necessary to associate with them. Education as begun by nature fully illustrates this. After a child has begun to notice things, it next wants to get hold of them.
Citation: Hartley, Charles Pinckley. Theory and practice in education. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Theory; Education; Child development; Theses; Manuscripts (documents)